When mistakes affecting one's own group result in compensation: Evidence of a compensatory own goal effect. (May 2020) - Hüffmeier, Joachim; Stern, Julia; Schultze, Thomas
Abstract: Objectives: Although sports team members often value their teams highly, they sometimes make mistakes and thereby unintentionally put their teams at a disadvantage. Thus, they should be motivated to compensate for their mistake to resolve this discrepancy. To test this hypothesis, we studied whether professional soccer players compensate for their own goals by scoring regular goals in the same game (Study 1) and possible processes underlying such compensation efforts (Study 2). Design: In Study 1, we compared how frequently prior own goal scorers scored a regular goal in the same game to (a) their expected goal scoring frequencies and (b) their probabilities to score a regular goal following a regular goal by the opposing team. In Study 2, we investigated four possible processes underlying the expected compensatory efforts. Method: We analyzed all own goals from the first fifty years of the German Bundesliga ( N = 889) and possible ensuing regular goals by the own goal scorer. Moreover, we surveyed amateur soccer players about four motives: group performance, individual performance, individual public image, and group public image. Results: Following their own goals, professional soccer players are particularly likely to score regular goals in the same game (i.e., a compensatory own goal effect). Presumably, they primarily do so to secure a good group performance, but the other motives also play a role. Conclusions: Group members who make highly visible mistakes are motivated to compensate for the disadvantage they caused. Presumably, they mainly do so to secure a good team performance. Highlights: We studied mistakes on sport teams as a source of compensatory motivation. We found that soccer players compensated for own goals by scoring regular goals. Securing good outcomes for their team was their main motive for compensating. Other motives (e.g., individual or group public image) played smaller roles. Mistakes on teams are an unexplored antecedent of motivation gains on teams.